2020
DOI: 10.1007/s10064-020-01925-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical stratigraphy and geotechnical properties controlling the local seismic response in explosive volcanic settings: the Stracciacappa maar (central Italy)

Abstract: Nowadays, policies addressed to prevention and mitigation of seismic risk need a consolidated methodology finalised to the assessment of local seismic response in explosive volcanic settings. The quantitative reconstruction of the subsoil model provides a key instrument to understand how the geometry and the internal architecture of outcropping and buried geological units have influence on the propagation of seismic waves. On this regard, we present a multidisciplinary approach in the test area of the Straccia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The damage pattern induced by seismic events is related to both geological/geomorphological conditions and the vulnerability of structures and infrastructures (Brando et al, 2020;Fayjaloun et al, 2021;Mori et al, 2020bMori et al, , 2019. The ground motion prediction (i.e., seismic site response) is generally evaluated by means of numerical simulations which are time consuming and require well-detailed models capable of properly representing subsoil and topographic conditions (see, for example, Bouckovalas and Papadimitriou, 2005;Falcone et al, 2020aFalcone et al, , b, 2018Gatmiri and Arson, 2008;Gazetas, 1982;Luo et al, 2020;Moscatelli et al, 2020b;Pagliaroli et al, 2014;Pitilakis et al, 1999;Régnier et al, 2016Régnier et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The damage pattern induced by seismic events is related to both geological/geomorphological conditions and the vulnerability of structures and infrastructures (Brando et al, 2020;Fayjaloun et al, 2021;Mori et al, 2020bMori et al, , 2019. The ground motion prediction (i.e., seismic site response) is generally evaluated by means of numerical simulations which are time consuming and require well-detailed models capable of properly representing subsoil and topographic conditions (see, for example, Bouckovalas and Papadimitriou, 2005;Falcone et al, 2020aFalcone et al, , b, 2018Gatmiri and Arson, 2008;Gazetas, 1982;Luo et al, 2020;Moscatelli et al, 2020b;Pagliaroli et al, 2014;Pitilakis et al, 1999;Régnier et al, 2016Régnier et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Cong et al [19] explored the boundary effects on the seismic response of a three-dimensional (3D) slope and concluded that an increase in the PGAs of earthquake events tends to enlarge the difference among the three lateral boundaries, whereas the differences between the three lateral boundaries are small for an earthquake with a larger predominant period. Moscatelli et al [20] studied the effect of stratigraphy and geotechnical properties on the seismic response in an explosive volcanic setting and reported that the occurrence of alternating soft and stiff materials in the central part of the maar strongly increases the site amplifications occurring at the surface.…”
Section: Introductionmentioning
confidence: 99%